2012
DOI: 10.1179/1743280411y.0000000011
|View full text |Cite
|
Sign up to set email alerts
|

Freeze casting of porous materials: review of critical factors in microstructure evolution

Abstract: Freeze casting is a promising technique to fabricate porous materials with complex pore shapes and component geometries. This review is aimed to elaborate the fundamental principles of the porous microstructure evolution and critical factors that influence the fundamental physics involved in freeze casting of particulate suspensions. The discussion separately analyses homogeneous and directional freeze casting for both aqueous and non-aqueous systems. The effects of additives, freezing conditions, suspension s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
223
0
7

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 321 publications
(235 citation statements)
references
References 129 publications
(320 reference statements)
5
223
0
7
Order By: Relevance
“…We explored a versatile, readily accessible and inexpensive solutionphase materials shaping technique, namely freeze casting, to explore the possibility of assembling graphene sheets into corklike monoliths. Previous studies have demonstrated that when an aqueous suspension of nanoparticles is frozen, phase separation can result in the rejection of solid nanoparticles from the forming ice, which are then accumulated between the growing ice crystals 28,29 . If the fraction of nanoparticles is higher than the percolation threshold, the entrapped particles can form a continuous 3D network.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…We explored a versatile, readily accessible and inexpensive solutionphase materials shaping technique, namely freeze casting, to explore the possibility of assembling graphene sheets into corklike monoliths. Previous studies have demonstrated that when an aqueous suspension of nanoparticles is frozen, phase separation can result in the rejection of solid nanoparticles from the forming ice, which are then accumulated between the growing ice crystals 28,29 . If the fraction of nanoparticles is higher than the percolation threshold, the entrapped particles can form a continuous 3D network.…”
Section: Resultsmentioning
confidence: 99%
“…Freeze casting has been successfully adopted to synthesize a variety of porous ceramic, metallic, polymeric and composite materials, including carbon nanotubes or graphene-based polymer composites 18,[30][31][32][33] . Although previous research on freeze casting has been centred on polymers and spherical particles 28,29 , we were particularly interested in studying how 2D graphene sheets interact with anisotropic ice crystal growth without the interference of other polymer or surfactant additives. In this work, GO, which can be readily produced from graphite in large quantities 2 , was chosen as a precursor to synthesize graphene-based monoliths.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Freeze casting is a relatively simple, inexpensive, and adaptable technique to fabricate bulk porous scaffolds and hybrid composites. Deville,14 Gutierrez et al, 15 Qian and Zhang, 16 and Li et al 17 provide excellent reviews of general freeze casting topics, including the processing principles, materials, structures, properties, and applications. This article focuses on freeze casting as it relates to different biomimetic materials and processing modifications inspired by nature.…”
Section: Introductionmentioning
confidence: 99%
“…[14][15][16][17] Figure 1 shows the basic processing steps involved in freeze casting porous ceramic scaffolds and hybrid ceramic-polymer composites-the main focus of this article. First, a liquid slurry containing ceramic powders and a freezing vehicle (e.g., water) is mixed with a dispersant (e.g., surfactant) and binder (e.g., long-chain polymer), which aid in colloid dispersion and green body integrity, respectively (Fig.…”
Section: Introductionmentioning
confidence: 99%